THE INFLUENCE OF DIGITAL LITERACY ON THE USE OF E-COMMERCE AS A MARKETING MEDIUM AMONG INDONESIAN MASTER VOCATIONAL SCHOOL STUDENTS - Murdiyono Murdiyono; Didi Sukardi; Rahmatullah Rahmatullah; I Nyoman Suri Adnyana (Nusantara Hasana Journal, 2022)
The development of digital technology has driven a shift in marketing patterns from conventional to digital-based marketing through e-commerce. This study aims to determine the effect of digital literacy on the use of e-commerce as a marketing medium among students of SMK Master Indonesia. The research method used was quantitative, with data collection techniques through distributing questionnaires to students. The results showed that students' digital literacy levels have a positive and significant influence on their ability to use e-commerce in marketing activities. Students who have a good understanding of digital technology tend to be better able to utilize marketplaces, social media, and e-commerce platforms to promote products and services. Digital literacy also helps students understand transaction security, digital marketing strategies, and online business communications. This research is expected to form the basis for developing digital entrepreneurship learning in schools.